2014
DOI: 10.1371/journal.pone.0091335
|View full text |Cite
|
Sign up to set email alerts
|

Upper Arm Central Venous Port Implantation: A 6-Year Single Institutional Retrospective Analysis and Pictorial Essay of Procedures for Insertion

Abstract: BackgroundThe requirement of central venous (CV) port implantation is increasing with the increase in the number of cancer patients and advancement in chemotherapy. In our division, medical oncologists have implanted all CV ports to save time and consultation costs to other departments. Recently, upper arm implantation has become the first choice as a safe and comfortable method in our unit. Here we report our experience and discuss the procedure and its potential advantages.MethodsAll CV port implantations (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 31 publications
(14 reference statements)
5
32
1
Order By: Relevance
“…The overall complication rates in the chest (7.4 %) and neck (6.8 %) groups reported in this study are similar to those mentioned in a previous report regarding complication rates of central venous catheterization by site [10]. Furthermore, although related studies regarding sites other than the chest and neck are scarce, our results concerning the incidence of complications stratified by CVPI sites/methods are similar to those of previous reports [19,23,[25][26][27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The overall complication rates in the chest (7.4 %) and neck (6.8 %) groups reported in this study are similar to those mentioned in a previous report regarding complication rates of central venous catheterization by site [10]. Furthermore, although related studies regarding sites other than the chest and neck are scarce, our results concerning the incidence of complications stratified by CVPI sites/methods are similar to those of previous reports [19,23,[25][26][27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 91%
“…Using the upper arm as the venipuncture site itself prevents pneumothorax, for anatomical reasons. However, the vein in the upper arm is thinner than at other sites, can hardly be seen grossly, and lacks anatomical landmarks, because of which the real-time US-guided method is more useful for upper arm CVPI than other non-real-time imaging methods [23]. As expected, the upper arm group showed the most frequent usage of the real-time US-guided procedure and least frequent usage of the landmark and US-mark methods.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Diagnostic ultrasonography guidance prevented pneumothorax and artery puncture during the CV-port placement procedure. Recently, Shiono et al [9] reported that the complication rates associated with CV-port implantation in the subclavian vein and upper arm were 10.2% and 4.7%, respectively. Therefore, it was concluded that upper arm implantation might be better, while considering patient safety and comfort.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with a variety of solid neoplastic diseases, outpatient chemotherapy is viable through the placement of a subcutaneously implanted CV-port and the use of a portable disposable pump [8] [9]. However, to the best of our knowledge, there have been no reports concerning the clinical course of LC patients with subcutaneously implanted CV-ports from the time of receiving chemotherapy to the endpoint of cancer.…”
Section: Introductionmentioning
confidence: 99%